Relationship between milk-feeding patterns in infancy and obesity among 5-6 year-old children of kindergarten and pre-elementary schools in Qazvin - Golyan Tehrani; Sh. Modares; M. Faghihzadeh; S. Safdari; Z (Tehran University of Medical Sciences, 2004)
Introduction: Obesity is a problem to individual's health and determintion of its causative factors is essential for prevention of obesity and maintenance of health. Materials and Methods: This research is a case-control analytic study (prospective) which has been conducted in kindergartens and pre-elementary schools affiliated to health organization in Qazvin city. After a preliminary study on twenty 5-6 year-old children, 35 obese (case) and 70 normal (control) children were chosen. The kindergartens and pre-elementary schools were selected based on random cluster case-picking method. The tools were a questionnaire, tape meter and spring scale. The obesity was defined as a weight/ height ratio more that two standard deviation above average for sex. The statistical tests were 2, t test and Mann-Whitney test. Results: The findings showed that the individual characteristics of the child, except weight birth and playing hours, were congruous in case and control groups. Also there was no significant difference between milk-feeding patterns in case and control groups, 77.1% and 85.7% dominant feeding on mother's milk, 20% and 8.6% feeding on formula and 2.9% and 5.7% feeding jointly on mothers milk and formula, respectively. In case of length of each feeding pattern group, no meaningful difference in two groups was found. Therefore all the survey hypotheses were rejected. Conclusion: According to the research findings, no meaningful relationship between feeding patterns in infancy and obesity in 5-6 year-old children was found and hence probably other factors are playing a role in predisposing to obesity. It is recommended that more extensive researches being carried out in this field.